Microneedling in androgenetic alopecia; comparing two different depths of microneedles. (29th September 2020) - Faghihi, Gita; Nabavinejad, Samin; Mokhtari, Fatemeh; Fatemi Naeini, Farahnaz; Iraji, Fariba
Abstract: Background: Microneedling has shown to have positive therapeutic effects in treatment of androgenetic alopecia (AGA); however, the best microneedling protocol is still controversial. Aims: Investigating effect of microneedling with 2 different depths of penetration on promoting hair growth in patients with AGA. Methods: Sixty patients, in the age of 18‐45 years old with moderate and severe AGA, were allocated into 3 groups of control: treatment with minoxidil 5% lotion; group A: treatment with minoxidil 5% lotion and biweekly microneedling with a depth of 1.2 mm and group B: treatment with minoxidil 5% lotion and biweekly microneedling with a depth of 0.6 mm during 12 weeks. Efficacy parameters including change of hair count and hair thickness from baseline and assessment of hair growth by patient and investigator were evaluated. Results: Compared with the baseline, a significant increase in hair count and hair thickness was observed in all three groups after completion of the treatment course ( P < .05). The mean rise in hair count ( P = .017) and hair thickness ( P = .007) was significantly greater in group B compared with control group. Investigator's evaluation of hair regrowth was significantly greater in group A ( P = .04) and group B ( P = .007) compared with control group. Conclusion: Microneedling with a depth of 0.6 mm in combination with minoxidil is more effective than minoxidil monotherapy in patients with AGA in terms of hair count and hair thickness. This depth of penetration tended to be more beneficial than depth of 1.2 mm.